THE EFFECT OF VILLAGE FUNDS, HUMAN DEVELOPMENT INDEX (HDI), AND ECONOMIC GROWTH ON DECREASE OF POVERTY LEVEL IN NORTH SUMATERA PROVINCE - Sihite, Lestari (Asosiasi Dosen Akuntansi Indonesia, 2021)
This study aims to analyse the effect of the Village Fund, Human Development Index and Economic Growth in reducing poverty levels in North Sumatra Province. This research is quantitative in nature with secondary data in the form of panel data from 2015-2018 processed with Eview’s program. The results showed that the Village Fund had a negative and not significant effect in reducing poverty levels with a coefficient of -1.66. Human Development Index has a negative and significant effect in reducing poverty with a coefficient value of -0.53. Economic growth has a positive and not significant effect with a coefficient value of 1.05.